Methodological assessment of the Critical Thermal Maximum (CTmax) of anuran larvae: interaction among the experimental heating rates, ontogeny and body mass - Cantero, Gustavo Adolfo Agudelo (2016)
Thermal limits for ectothermic animals displays a picture of the range of body temperatures that is tolerable by individuals before their locomotory capacity is impaired. However, thermal limits are not fixed and specific traits, but labile ones subjected to plastic adjustments and evolutionary change, and also are influenced by intrinsic and extrinsic factors of organisms, as well as by methodological factors inherent to experimental protocols. Even more, the influences of these factors on thermal limits have been commonly addressed independently in different taxa, and the extent by which multiple factors interact and affect thermal limits within taxa is poorly understood. Thus, the main aim of this work was to conduct a methodological assessment of the Critical Thermal Maximum (CTmax) by studying the influences of different experimental heating rates (ΔT’s), ontogeny, body mass, and the interaction among these factors on this trait. This matter was addressed on larvae of Physalaemus nattereri and Hypsiboas pardalis, two anuran species from the São Paulo State, southeastern Brazil, that differ in their phylogenetic background, ecological and life-history characteristics and inhabit environments with different thermal regimes. First, ΔT’s did affect averages and variances of CTmax in a species-specific manner. In addition, it was found a ΔT-dependent decreasing in CTmax at the end of metamorphosis in tadpoles of P. nattereri, because only the metamorphosing tadpoles exposed to the acute ΔT were more sensitive to high temperature than premetamorphic tadpoles. Finally, body mass and ΔT’s interacted on the CTmax of both species along our experimental design. In P. nattereri, body mass affected CTmax through physiology at the slow ΔT’s, whereas in H. pardalis body mass affected CTmax at the acute ΔT through a methodological artifact driven by higher thermal inertia in the group of large tadpoles. This study revealed that ΔT’s, ontogeny and body mass interact on the CTmax of our studied species, and these interactive effects could not have been elucidated by the independent study of each factor. It also highlights the importance of integrating the factors that influence thermal limits of ectothermic animals, especially in the context of climate change